A taxonomic review of the Genus Dryophilocoris (Hemiptera: Heteroptera: Miridae: Orthotylinae: Orthotylini) in the Fareast Asia with the description of a new species - Jung, Sunghoon; Duwal, Ram Keshari; Yasunaga, Tomohide; Heiss, Ernst; Lee, Seunghwan (Zootaxa, 2010)
A total of seven species of the genus Dryophilocoris Reuter are reviewed from Fareast Asia with a new species, Dryophilocoris kerzhneri Jung et Yasunaga sp. nov. Three known species, D. lucidus Yasunaga, D. miyamotoi Yasunaga, and D. saigusai Miyamoto, are newly recognized from the Korean Peninsula. The female genitalia are illustrated and described as taxonomic characters for the first time in the genus, and a key to the species in Fareast Asia is also provided.